(3GdOhQ GdJTQjYj dQFjS GdOhdI aj GdbGfhf GdadSWjfj (B: s (3OQGSI ebGQfI (B/ s - (3JeGe jhSa Ndjd fhads; (3QCaJ ahOg (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2018)
(3gOaJ GdOQGSI(B: (3GdcTa Yf GdOhQ GdJTQjYj dQFjS GdOhdI aj GdbGfhf GdadSWjfj aj VhA GdfXe GdOSJhQjI GdeYGUQI(B. (3GdHQdeGfjI hGdQFGSjI hGdeNJdWI MJi fcTa eOi GfSLGe SjGSI GdeTQY GdadSWjfj eY Jdc GdfXe(B. (3efgL GdOQGSI(B: (3Ef efgL gPG GdHMK dGHO Cf jchf ehVhYjkG hebGQfkG(B: (3dPG SfNhV aj fUhU GdbGfhf GdCSGSj GdadSWjfj hGdfXe GdOSJhQjI GdebGQfI; dJSdjW GdVhA YdjgG(B: (3hJbjjegG aj VhA JLGQH GdBNQjf hNHQGJge; ddGSJaGOI ef CaVd GdfXe(B: (3hSfCNP GdfXGe GdeNJdW aj aQfSG cfehPL ebGQf(B: (3HGdEVGaI Edi HYV GdfXe GdSjGSjI GSJFfGSkG(B. (3GSJfJGLGJ GdOQGSI(B: (3egeG GLJgOJ GdOSGJjQ aj JbjjO SdWGJ QFjS GdOhdI jHbi gh bHI GdfXGe heMhQ GQJcGRg GdChd(B: (3hdg OhQ hGSY aj GdJTQjY ShGkA aj GdXQha GdYGOjI Ch GdGSJKfGFjI(B: (3agh GdSdWI GdQGLMI hdjSJ GdeQLhMI OGFekG(B: (3haj cd GdfXe HdG GSJKfGA hEf cGf GdCeQ fSHjkG aj HYV GdfXe s
2018. (3CWQhMI (B((3OcJhQGg(B)-s
(3HHdjhLQGajG(B: (3UaMGJ (B479-510.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdecGfI GdOSJhQjI dQFjS GdOhdI s; (3GdOhQ GdJTQjYj dQFjS GdOhdI aj GdXQha GdYGOjIs; (3SdWI QFjS GdOhdI aj GdJUOjb hGdGYJQGV Ydi GdbhGfjf s; (3GdOSJhQ GdaQfSjs; (3GdOhQ GdJTQjYj dQFjS GdOhdI aj MGdI GdJahjVs; (3GdOhQ GdJTQjYj dQFjS GdOhdI aj MGdI GdVQhQIs; (3GdOhQ GdJTQjYj dQFjS GdOhdI aj MGdI GdWhGQFs; (3GdehGRfGJ GdQbGHjI Ydi dhGFM GdJahjVs; (3GdehGRfGJ GdQbGHjI Ydi dhGFM GdVQhQIs; (3GdehGRfGJ GdQbGHjI Ydi SdWGJ GdWhGQF s; (3GdecGfI GdOSJhQjI dQFjS GdOhdI s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2018